Hydrothermal activity in the Obiro deposit embedded in the Tagawa acidic rocks, Uetsu region, NE Japan. Issue 4 (18th August 2020) - Nakajima, Yuki; Izumino, Yuya; Kagashima, Shin‐ichi; Nakashima, Kazuo
ABstract: The Obiro deposit is located in the Tagawa Acidic Rocks (AR), Uetsu region, NE Japan. The Tagawa AR is composed of a volcanic phase of dacitic welded tuff and a plutonic phase of porphyritic granodiorite. Drill core and ore samples were collected from the deposit and examined by XRD, EPMA, and microthermometry. The drill core samples have suffered pervasively from sericite (illite) alteration, whereas pinkish K‐feldspar alteration halo occur close to veins. The results of EPMA and microthermometry is interpreted as that the magnatic‐hydrothermal fluids has changed as follows; the granodioritic magma intruded at about 1.0 kb and 700°C near the water‐saturated granite solidus; after cooling to about 500°C the fluids boiled according to a change in the pressure regime from lithostatic to hydrostatic; mixing with meteoric water led to sulfide mineralization at around 400°C or less. The main reasons for the mineralization in the Obiro deposit are as follows; the oxidized magma intruded at a shallower level, and thereafter hydrothermal fluids were boiled, resulting in a saline fluid. The saline fluid then dissolved metals such as Pb, Zn, Cu, and Bi, and these metals precipitated during cooling accompanied by dilution of the meteoric water and increasing pH, resulting in decreasing solubility. Abstract : The results of EPMA and microthermometry of the drill core from the Obiro deposit indicate that the evolution of fluids has changed as follows; the granodioritic magma intruded at about 1.0 kb and 700°C near the water‐saturated granite solidus. The main reasons of the mineralization in the Obiro deposit are as follows; the oxidized magma intruded at a shallower level, and thereafter hydrothermal fluids boiled.